HISTÓRIA ORAL E IDENTIDADE CULTURAL: INDÍGENAS NA UNIVERSIDADE ESTADUAL DE PONTA GROSSA (UEPG) - Miola, Ana Carolina Moreira (2016)
The Vestibular of Paraná Indigenous Peoples existed since 2001, with the creation of the State Law No. 13,134 / 2001. In this study, we stop in the reality of Ponta Grossa State University (UEPG) in Ponta Grossa, bringing 11 reports of indigenous that got in the institution through this selection process. The methodology used was the oral history, which provides an appreciation of the oral report of the subjects, constructed from your memories and experiences. In this sense, we show the contexts in which indigenous are at UEPG, based on theories of cultural studies and cultural identity, especially using Stuart Hall, we list the lines, looking for traces of identity and how they present themselves at this scene. We point the considerations the lack of a public policy, having found that isolated initiatives, supported by reports, shows this gap. We found a group with different views, with opposition within it. Having entered the VPIP changes to some extent, the dynamics of indigenous higher education, and forcefully presents the changing face identity in its construction.